Pengembangan Media Pembelajaran Fun Thinkers Book Pada Materi Keberagaman Rumah Adat di Indonesia Pada Pembelajaran IPS Kelas IV UPT SD Negeri 104 Gresik - Fenny Alvionita; Arya Setya Nugroho (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
This research was motivated by the problems found when the teacher delivered learning materials to the fourth grade students of UPT SD Negeri 104 Gresik. Based on research from several subjects that have a low level of enthusiasm for students' interest, it can be seen from the level of rereading or reviewing material in social studies learning about the diversity of traditional houses in Indonesia. This can hinder the teaching and learning process and the delivery of material by teachers to students, due to the limited media and learning resources that are fixated on books and sources from the internet, which is one of the obstacles for students to understand and remember traditional house materials in Indonesia. The next stage to overcome these problems, the best step to take is to provide an approach with students through the Fun Thinkers Book media which is able to involve students directly in teaching and learning activities so as to increase students' reading interest and understanding of students. The researcher mitigates the problem by using the ADDIE Analysis model, Design, Development, Implementation, Evaluation. The purpose of this study is to determine whether or not the media development product is valid in social studies learning material on the diversity of traditional houses in Indonesia for class IV UPT SD Negeri 104 Gresik. The results of media validation that have been carried out by media experts get a percentage of 94.79% with the